Interpretasi Konsep Tuhan Perspektif Maulana Makhdum Ibrahim dalam Kitab Primbon Bonang dan Suluk Wujil - Jauharotina Alfadhilah (Islamika Inside: Jurnal Keislaman dan Humaniora, 2018)
This article analyzes the concept of God according to Sunan Bonang's view in his works, namely Primbon Bonang and Suluk Wujil. This article concludes that the two books are a compendium of Sunan Bonang's Sufism and his spiritual journey during his life. Sunan Bonang explains that the first step that must be done by the sÄlik before embarking on a spiritual journey is trying to know himself and multiply wirid and zikir. Sunan Bonang's type of sufism can be categorized Sunnī Sufism, which rejects the concept of Waḥdat al-Wujūd. Alternatively, he proposes a new concept called "Padudoning Kawula Gusti", which means that human is not God and God is not human; both cannot be unified. To him, God is the transcendent and immanent One with several limitations. The unity of God is explained by him through the sentence of lā Ilāh illā Allāh, which means there is no god but Allah. The sentence is started with nafy (negation) â€œthere is no godâ€ then continued with the phrase ithbāt (affirmation) "but Allah", which means that there is only One God in the universe.